The Development of Learning Media “Adobe Animate” In Hydrocarbon Material - Felix Valentino Sianturi; Marini Damanik (COMSERVA : Jurnal Penelitian dan Pengabdian Masyarakat, 2022)
Research had been carried out to develop a learning media using ADDIE (Analysis, Design, Development, Implementation, and Evaluation) model with the aims to find out the media feasibility in the hydrocarbon material. This research only carried out three stages of ADDIE model namely up to the development stage. The research samples in the research are lecturers of Universitas Negeri Medan, chemistry teachers of SMAN 7 Medan, and information and technology (IT) experts. The samples become the media validator for this research. There are 3 validators that had validated the media, consist of 1 expert lecturer, 1 chemistry teacher, and 1 IT expert. The results showed that learning media validation results based on BSNP, the average content eligibility is 4.67, language eligibility is 4.67, presentation eligibility is 4.73, graphic eligibility is 4.73, with an average of 4.68; it means that the learning media developed is feasible to use based on the BSNP standard criteria.